Performance evaluation, a new tool for the culture of transparency applied to the public sector in Mexico - Rodríguez Montaño, Luis Carlos (Universidad de Sonora, 2021)
This paper describes and analyzes the general context of the performance evaluation function. First, the general ideas of the concept are analyzed. Subsequently, its origin in private organizations is reviewed, and later it is described and analyzed how its incorporation into the public sector in Mexico has been over time, seen as an innovative measurement tool in the achievement of its objectives. However, performance evaluation applied in the public sector can be seen from two perspectives, for some it can be an area of opportunity in terms of improving the role of the government, for others it can be perceived as a kind of punishment which each time more is taking institutional channels and is being inserted in the governmental work as a measure of efficiency.